W.E.B. Du Bois speaks : speeches and addresses 1890-1919 - Du Bois, William Edward Burghardt; Foner, Philip S. (New York : Pathfinder Press, 1970)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: burgerrechten; zwarte bevolking